2008
DOI: 10.1021/jp802310p
|View full text |Cite
|
Sign up to set email alerts
|

Organosulfate Formation in Biogenic Secondary Organic Aerosol

Abstract: Organosulfates of isoprene, alpha-pinene, and beta-pinene have recently been identified in both laboratory-generated and ambient secondary organic aerosol (SOA). In this study, the mechanism and ubiquity of organosulfate formation in biogenic SOA is investigated by a comprehensive series of laboratory photooxidation (i.e., OH-initiated oxidation) and nighttime oxidation (i.e., NO3-initiated oxidation under dark conditions) experiments using nine monoterpenes (alpha-pinene, beta-pinene, d-limonene, l-limonene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

80
1,235
4
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 661 publications
(1,321 citation statements)
references
References 99 publications
80
1,235
4
2
Order By: Relevance
“…Previous chamber studies have demonstrated that both OH-photooxidation and NO 3 dark reactions can form pinene-derived nitrooxy-organosulfates (pNOSs) on acidic particles. 9 The pNOSs were only detected in nighttime samples in northeastern Bavaria, Germany, suggesting a role for nighttime NO 3 chemistry in pNOS formation. 15 However, if acidic aerosols are required by the NO 3 pathway, 9 what is the explanation for the phenomena that neutralized aerosols coincided with the high overnight concentrations of pNOSs?…”
Section: ■ Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous chamber studies have demonstrated that both OH-photooxidation and NO 3 dark reactions can form pinene-derived nitrooxy-organosulfates (pNOSs) on acidic particles. 9 The pNOSs were only detected in nighttime samples in northeastern Bavaria, Germany, suggesting a role for nighttime NO 3 chemistry in pNOS formation. 15 However, if acidic aerosols are required by the NO 3 pathway, 9 what is the explanation for the phenomena that neutralized aerosols coincided with the high overnight concentrations of pNOSs?…”
Section: ■ Introductionmentioning
confidence: 94%
“…35 For pNOSs, additional MS/MS product ions with m/z 247 (loss of HNO 2 ) and m/z 231 (loss of HNO 3 ) were detected. 9 The structures of three pNOS isomers with MW 295 (pNOS a , pNOS b , pNOS c ) were identified by comparing the detected spectra (Figure S2c−e) with those provided by Surratt et al 9 The isomer pNOS a was identified by extremely low intensity of m/z 231 ions and high intensity of m/z 220 (loss of CO and NO 2 ) in MS2 spectra ( Figure S2c); while the isomer pNOS c was identified by significant intensity of m/z 142 ( − OSO 3 NO 2 ) ( Figure S2e). Due to the lack of commercial standard, OSs were quantified using camphor sulfonic acid.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interferences due to evaporative loss from the filters or heterogeneous reactions on the filters during sampling are known issues and difficult to quantify. Individual large multifunctional nitrates have been observed in ambient aerosol samples collected on filters using electrospray ionization mass spectrometry (23,24). However the most widely used methods for aerosol chemical characterization including Aerosol Mass Spectrometry (AMS) have had limited success.…”
Section: Introductionmentioning
confidence: 99%